(untitled) (Scientific journal of the Fergana State University, 2024)
The article reflects on the specifics of land resources and their change from "place to place" based on the regional principle, the dominant aspects of geography in the study of such regional identities. Information is also provided on the classification of land resources as a component of the landscape, as a means of production, and methods for assessing the condition of the Land Fund and soil.